In Vitro Selection and Characterization of Resistance to Macrolides and Related Antibiotics in Mycoplasma pneumoniae - Pereyre, S. (American Society for Microbiology, 2004)
Macrolide-resistant mutants of Mycoplasma pneumoniae were selected in vitro from the susceptible reference strain M129, by 23 to 50 serial passages in subinhibitory concentrations of macrolides and related antibiotics, erythromycin A, azithromycin, josamycin, clindamycin, quinupristin, quinupristin-dalfopristin, pristinamycin, and telithromycin. Mutants for which the MICs are increased could be selected with all antibiotics except the streptogramin B quinupristin. Portions of genes encoding 23S rRNA (domains II and V) and ribosomal proteins L4 and L22 of mutants were amplified by PCR, and their nucleotide sequences were compared to those of the susceptible strain M129. No mutation could be detected in domain II of 23S rRNA. Two point mutations in domain V of 23S rRNA, C2611A and A2062G, were selected in the presence of erythromycin A, azithromycin, josamycin, quinupristin-dalfopristin, and telithromycin. Mutants selected in the presence of clindamycin and telithromycin harbored a single amino acid change (H70R or H70L, respectively) in ribosomal protein L4, whereas insertions of one, two, or three adjacent glycines at position 60 (M. pneumoniae numbering) were selected in the presence of both streptogramin combinations. Telithromycin was the sole antibiotic that selected for substitutions (P112R and A114T) and deletions ((111)IPRA(114)) in ribosomal protein L22. Three sequential mutational events in 23S rRNA and in both ribosomal proteins were required to categorize the strain as resistant to the ketolide. Azithromycin and erythromycin A were the only selector antibiotics that remained active (MICs, 0.06 and 1 μg/ml, respectively) on their mutants selected after 50 passages.